The Analysis of Office Management in Improving the Quality of Public Services (Case Study of Cisaat Police Office, Sukabumi Regency) - Anggraeni, Agnisa; Laswati, Esi Fitri; Masitoh, Neneng; Nurkholifah, Siti Sifa Nurkholifah; Gustiani, Tarisma; Mentari, Yessi Septia; Pajriah, Zaki (Social Impact Journal, 2023)
In the face of increasingly complex community dynamics and increasing service demands, the role ofGovernment Agencies in the local Sector as law enforcement agencies and guardians of public order isvery important. One aspect that also determines the quality of an institution's public services is theoffice management system applied. The purpose of this study is to analyze and identify theeffectiveness, efficiency, and satisfaction of the community with the services provided at the CisaatPolice Office. In addition, this study also aims to identify potential improvements or innovations inpublic services in the local area. This research is a descriptive research with a qualitative approach.This research was chosen because it presents systematic, factual, and accurate data on the facts in thefield. By using descriptive research with a qualitative approach, it aims to explore facts about thequality of public services in government agencies, namely the Cisaat Police Office, Sukabumi Regency.Based on the analysis conducted, it was found that the Cisaat Police Structure of Sukabumi Regency onthe effectiveness of public services is very influential, because it can help the running of activities andcoordination of the management of the Cisaat Police Office organization of Sukabumi Regency in chargeof carrying out coaching, empowerment, and development activities which include partnerships andcooperation between communities and community organizations for compliance with order andsecurity implementation.